Locust Lane : A Novel - Amidon, Stephen (New York : Celadon Books, 2023)
When three teenagers--Hannah, a sweet girl with an unstable history; Jack, the popular kid with a mean streak; and Christopher, an outsider desperate to fit in$1 (Bbecome suspects in the murder of a fellow student in Emerson, Massachusetts, their parents will do anything to protect them, even at the others' expense.s
Keywords: Suburbs -- Fiction; Teenagers -- Fiction; Murder -- Fiction; Families -- Fiction; Parent and child -- Fiction; Massachusetts -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Novels